Examining the Readiness of Pre-service Teacher sto Implement Inclusive Education (Indo-American Journal of Life Sciences and Biotechnology, 2021)
Recent research shows that teachers who have a pro-inclusion mindset are more likely to alter theirlessons and curriculum to meet their students' individual needs. Educator training programs areaccountable for ensuring that teachers are prepared to teach inclusively. According to the findings of thestudy, pre-service teachers from two universities were polled about their attitudes toward inclusion andtheir readiness to teach in inclusive classrooms. A self-prepared questionnaire was utilized to gatherdata on the study's participants, who were all second-year preservice teachers in the teacher trainingprogram. Despite a positive attitude toward inclusion, the study found that student teachers lacked theskills and experience necessary to teach in an inclusive environment. Recommendations for improvingteacher training programs were drawn from this study.